The Important Role of Community Figures in Efforts to Maintain Religious Harmony in Ngampin Village, Ambarawa District, Semarang Regency - Moh Rizqy ‘Ubaidillah; Zulfa Fadilla Ludfiana; Ervianti Ervianti; Laeli Noor Khafidhoh; Ulfia Aisyifa; Chusnul Adib Achmad (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
This research examines the role of community leaders in maintaining religious harmony in Ngampin Village, Ambarawa District, which has the characteristics of a multicultural society. This research uses a descriptive qualitative approach using in-depth interviews with community leaders and field observations during the period 17 October to 30 November 2024, which explores the dynamics of tolerance between religious communities. Based on statistical data, Ngampin Subdistrict has a diverse religious composition, namely 4,673 Muslims, 586 Catholics, 450 Protestants, 13 Hindus, and 7 people of other faiths. Research reveals that religious harmony is built through a comprehensive strategy, through the formation of the Religious Harmony Association (PKUB), preserving local Nyadran and Merti Dusun traditions, as well as a dialogical approach between religious communities. The findings show that success in maintaining harmony requires a high awareness of tolerance, local wisdom, and the active role of community leaders in reducing potential conflict.